The Influence of Intrinsic and Extrinsic Motivation Factors on Employee's Performance at Pecca Leather Sdn. Bhd. as Mediated by Job Satisfaction - Othman, Abdul Kadir; Abdullah, Mohd Zulkifli; Aziz, Noor Fadhilah; Tobi, Siti Noraini Mohd (Journal of Entrepreneurship, Business and Economics, 2022)
Employee performance has been a topic of interest for researchers and practitioners in the field of industrial or organizational psychology for decades. There is no single solution for the problem related to this topic. The present study is meant to investigate the factors that might contribute to increasing employee performance at Pecca Leather Sdn. Bhd. To further explain the relationship between the predictors and the outcome variable, job satisfaction was included as the mediating variable. The results indicate that task significance and growth, and task execution have significant direct relationship with job performance. Meanwhile, job satisfaction acts as a quasi-mediator on the relationship between task significance and growth and job performance and between task execution and job performance. Top management at the company must consider these two factors in motivating their staff to achieve high job performance. Other implications are discussed in the paper. Research paper Keywords: Extrinsic; Intrinsic Motivation; Job Performance; Job Satisfaction; Case Study Reference to this paper should be made as follows: Othman, A. K., Abdullah, M. Z., Aziz, N. F., & Tobi, S. N. M. (2022). The Influence of Intrinsic and Extrinsic Motivation Factors on Employee's Performance at Pecca Leather Sdn. Bhd. as Mediated by Job Satisfaction. Journal of Entrepreneurship, Business and Economics , 10 (2S1), 28–52.